Argon plasma coagulation in therapeutic endoscopy. (1st October 2019) - Abraham, Anuj
Abstract : Argon plasma coagulation (APC) is used widely and effectively in therapeutic gastrointestinal endoscopy, mainly to achieve both haemostasis and tissue ablation. The main advantages of APC treatment are its ease of application, cost effectiveness, improved safety and reduced time for application. This review gives an insight into the safe and effective use of APC in the gastrointestinal tract with flexible endoscopy. It discusses the technical aspects of the APC generator, the different types of APC probes tailored to the indication and the target tissue. It also discusses patient preparation, including the optimal pre- and post-APC care instructions.